EXTRACTING INFORMATION ON THE NATURE OF GENDER EQUALITY: QUR’ANIC PERSPECTIVE - Otong Surasman (Takafu: Journal of Tafsir and Gender Perspective, 2025)
This research will explore the nature of gender equality in the view of the Holy Qur'an, an ideal thought so that it is not misguided in understanding it, so that the realisation of community life is full of justice, harmony, peace and prosperity, especially on our beloved Indonesian earth. In Indonesia, the struggle for gender equality is extraordinary, with the emergence of several organisations related to gender equality, including the National Commission on Violence Against Women (Komnas Perempuan), the Association of Indonesian Women's Unions (HAPSARI), and the Indonesian Women's Care Movement (GPPI). The specific purpose of this paper is to avoid misunderstandings in understanding gender equality, because in essence the existence of men and women has their respective duties in terms of their nature. A simple example of women every month must experience menstruation or menstruation, women experience pregnancy, women give birth and breastfeed, this is certainly different and not experienced by men. But essentially both men and women, how to strive to be the best human being, which is to provide benefits for the lives of other humans, even the surrounding nature. This research uses a qualitative approach by conducting an in-depth study of the text of the Holy Qur'an, as the main source of reference, also using the literature of the book of interpretation to provide ease in understanding the text of the Holy Qur'an related to gender equality in accordance with the view of the Qur'an, so that people's lives in the nation and state on earth Indonesia, can achieve golden Indonesia 2045. The temporary conclusion is that by understanding gender equality in the Qur'anic perspective properly and correctly and trying to apply it in life, a life full of harmony will be realised, because essentially both men and women can place their respective positions in running the wheels of life. Which is the main requirement essentially for women and men to get the glory of life by believing and doing good deeds.